Situation Analysis of Smoking Behavior and Tobacco Control in Blitar City - Dedi Saifulah; Novita Ana Anggraini; Syahril Wahyu Ramadhan (Universitas STRADA Indonesia, 2023)
Background: The problem of smoking is still a national problem that is continuously being addressed, because it involves various aspects of problems in life, namely economic, social, political aspects, especially health aspects. The death rate from smoking is still very high. Tobacco abuse is a preventable cause of death but there are still many people who are difficult to escape from the bondage of the dangers of smoking. Purpose: The City of Blitar has committed to implementing a tobacco control program through the Regional Regulation (perda) of the City of Blitar Number 1 of 2019 concerning Smoking Free Areas. The implementation of these local regulations requires data as a basis for developing strategies to achieve goals. Methods: This study uses a mix method approach (quantitative and qualitative). The approach is used to facilitate a variety of specific research objectives. Research on smoking behavior and attitudes of tobacco workers towards tobacco control uses a quantitative approach. While research on regional income from the cigarette industry and the condition of cigarette advertisements in public places uses a quantitative approach. Results: Teenage respondents 300 respondents were dominated by male gender, smoking status there were 221 respondents who stated that they were smokers. Most of the respondents' ages were in the range of 17-20 years and at the junior and senior high school levels. With the results of this study it can be concluded that the incidence of smoking in adolescents is still high with a percentage (70.3%) of smoking status which is dominated by men. Adult respondents note that all male respondents have a tendency to smoke. Most of the respondents were in the range of 19-23 years with the most education at the high school level. Conclusion: The type of cigarettes consumed by adolescents is white cigarettes, consuming at least less than 5 cigarettes and at most more than 15 cigarettes per day. Most of the costs spent by teenagers to shop for cigarettes range from IDR 50,000 to IDR 100,000 and above. Among the 189 smokers respondents, only 83 of them had the desire to quit smoking. It is known that most of the adult respondents at the age of 15 years were the age when they first smoked.